2022
DOI: 10.3390/ijms232416130
|View full text |Cite
|
Sign up to set email alerts
|

PHF21A Related Disorder: Description of a New Case

Abstract: PHF21A (PHD finger protein 21A) gene, located in the short arm of chromosome 11, encodes for BHC80, a component of the Lysine Specific Demethylase 1, Corepressor of REST (LSD1-CoREST) complex. BHC80 is mainly expressed in the human fetal brain and skeletal muscle and acts as a modulator of several neuronal genes during embryogenesis. Data from literature relates PHF21A variants with Potocki–Shaffer Syndrome (PSS), a contiguous gene deletion disorder caused by the haploinsufficiency of PHF21A, ALX4, and EXT2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Herein, we genetically and clinically characterized a proband having moderate–severe ID, global developmental delay, ID, tonic seizures, ADHD, mild‐microcephaly, and speech issues. Features reported in our patient overlapped with the features reported previously 1,3–5 . However, unlike macrocephaly reported in the previous cases our patient revealed mild microcephaly 1 …”
Section: Figuresupporting
confidence: 76%
See 2 more Smart Citations
“…Herein, we genetically and clinically characterized a proband having moderate–severe ID, global developmental delay, ID, tonic seizures, ADHD, mild‐microcephaly, and speech issues. Features reported in our patient overlapped with the features reported previously 1,3–5 . However, unlike macrocephaly reported in the previous cases our patient revealed mild microcephaly 1 …”
Section: Figuresupporting
confidence: 76%
“…The Zebrafish indicated that PHF21A dosage are essential for craniofacial and neurodevelopment, while PHF21A suppression leads to abnormal head, face, jaw, and increased neuronal apoptosis. Importantly, these deficiencies were rescued by the human PHF21A , indicating a conserved developmental function 1,4,5 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 Although the phenotypic spectrum of intellectual disabilities, developmental delays, facial anomalies, overgrowth, and obesity in our case was generally consistent with that of previously reported cases, the pathogenic variant carried by our patient differed from those in previous reports. 4,5,12,13 This finding reinforces that PHF21A haploinsufficiency could contribute to intellectual developmental disorders and facial dysmorphism. Compared with previous cases, our patient showed no obvious cranial anomalies, finger anomalies, epilepsy, hypotonia, or diagnosis of ASD or attention-deficit hyperactivity disorder.…”
supporting
confidence: 65%
“…7 To date, 15 cases have been reported involving microdeletion frameshift or nonsense variants in the PHF21A gene. 4,5,[8][9][10][11][12][13] This report describes AS coexisting with a PHF21A-related disorder.…”
mentioning
confidence: 86%